2017
DOI: 10.1016/j.celrep.2017.10.027
|View full text |Cite
|
Sign up to set email alerts
|

Infectious Entry and Neutralization of Pathogenic JC Polyomaviruses

Abstract: Summary Progressive multifocal leukoencephalopathy (PML) is a lethal brain disease caused by uncontrolled replication of JC polyomavirus (JCV). JCV strains recovered from the brains of PML patients carry mutations that prevent the engagement of sialylated glycans, which are thought to serve as receptors for the infectious entry of wild-type JCV. In this report, we show that non-sialylated glycosaminoglycans (GAGs) can serve as alternative attachment receptors for the infectious entry of both wild-type and PML-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
66
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 77 publications
0
66
0
Order By: Relevance
“…On the other hand, increased GALNT3 expression paradoxically initiated mucin‐type O‐glycosylation, facilitating IAV replication . Among other CDG‐related genes, varying degrees of pathogen resistance (mainly of viral origin) have been reported . Despite intensive studies on viral infectivity and recognition of host glycans, the underlying molecular mechanisms and exact pathophysiological consequences in CDG remain largely unidentified .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, increased GALNT3 expression paradoxically initiated mucin‐type O‐glycosylation, facilitating IAV replication . Among other CDG‐related genes, varying degrees of pathogen resistance (mainly of viral origin) have been reported . Despite intensive studies on viral infectivity and recognition of host glycans, the underlying molecular mechanisms and exact pathophysiological consequences in CDG remain largely unidentified .…”
Section: Discussionmentioning
confidence: 99%
“…MCPyV is the first human PyV clearly linked to the development of a specific cancer (12). Initial studies on the principal mechanism of infection confirmed the requirement of sulfated glycosaminoglycans for attachment and sialylated glycans for infectious uptake into host cells, which may, in fact, reflect a common mechanism for several PyVs (28,30,31,91). To extend our knowledge of the mechanism of initial infection, we addressed additional cellular requirements and routes of virus entry.…”
Section: Discussionmentioning
confidence: 99%
“…The functional impact of JCPyV VP1 mutations was assessed by incorporating PML-associated mutations into either virus-like particles (VLPs) [46], VP1 pentamers [47], molecular clones of the JCPyV genome to produce infectious virus [47] and pseudotype particles produced by co-transfecting plasmids coding for JCPyV VP1, VP2 and VP3 proteins [47,48]. All of these approaches demonstrated that PML-associated mutations disrupt the sialic acid binding pocket of the VP1 pentamer and specifically abrogate binding of the JCPyV capsid to its receptor, the lactoseries tetrasaccharide c (LSTc), which terminates with an a2-6-linked sialic acid residue [49].…”
Section: Vp1 Evolution and Pathology In Jcpyv And Bkpyv Infectionmentioning
confidence: 99%
“…More recently Geoghegan et al [48] used pseudotype JCPyV particles carrying wild-type, L55F and S269F mutant VP1 to investigate the infectious entry characteristics of PML-associated mutations. They found that entry in a gliosarcoma cell line transfected with Large T Ag (SF-539 cell line) mediated by wild-type VP1 was dependent on the presence of sialylated glycans, while entry mediated by L55F and S269F mutant VP1 was sialic acid-independent.…”
Section: Vp1 Evolution and Pathology In Jcpyv And Bkpyv Infectionmentioning
confidence: 99%
See 1 more Smart Citation